Effect of Fresh and Fermented Olive Solid Waste and Cow Manure on Zinc Forms in Calcareous Soil and Wheat Plant Productivity (Journal of Hama University, 2020)
A field experiment was conducted at the farm of Abu Jarash in Agricultural College, using different rates of olive solid waste and cow manure, as follows: (control,  Mineral fertilizer +NPK, fresh olive solid waste100%,  fresh olive solid waste 75%+ cow manure 25%, fresh olive solid waste 50%+ cow manure 50%,   fermented olive solid waste 100%,  fermented olive solid waste 75%+ cow manure 25%,  fermented olive solid waste 50%+ cow manure 50%, cow manure 100%)The Zink ground fertilizers  are added for all previous treatments, and cultivation of wheat, the forms of zinc were followed by serial extraction and the study led to the following results:the fermented olive solid waste 100% treatment was Superiority in the amount of zinc forms as follows: (total, soluble, exchanged, linked with carbonate, linked with organic matter linked with iron and manganese oxides and residual) the amounts of Zinc were (114.14, 0.19048, 1.0710, 6.329, 9.433, 21.04, 76.10) mg/kg in the same previous order, while the zinc values ​​in the control treatment were (62.90, 0.03847, 0.6081, 3.29, 6.083, 15.03, 37.2) mg/kg for the same forms and in the same previous order. The fermented olive solid waste treatment 100% had the highest yield (5.980) ton/h. The control treatment had the lowest value (3.987) ton/h.